ANALYSIS OF OPINIONS AND DIFFICULTIES EXPERIENCED BY BASIC EDUCATION TEACHERS IN CHEMISTRY CLASSES DURING REMOTE EMERGENCY TEACHING - Renaria Veras da Silva, Antonia; Da Silva Lacerda Junior , Orivaldo (Journal of Interdisciplinary Debates, 2022)
This research has as main objective to analyze the perceptions of Chemistry teachers in relation to the methodologies and main difficulties faced by them during remote emergency teaching in Ceará. This monographic work is important for registering this historic moment in education and consequently in the lives of teachers and in the teaching-learning process. the research reaffirms the importance of planning and executing classes, with emphasis on the discipline of Chemistry. Data collection took place through a form via Google forms with ten teachers, seeking to understand the main difficulties and teaching methodologies in the face of this form of teaching with a look at learning expectations with the return of face-to- face teaching in educational institutions. Chemistry teachers described their routines during this period, such as the workload that always exceeded that expected by schools, the lack of student participation in synchronous classes, it was reported on the support they had from the Ceará state secretariat to carry out classes during this period. Teachers report the difficulties encountered in adapting the tools available in a short period of time. The analysis of the obtained data was made from theoretical references that have as objective the implementation of information and communications in front of the teaching of Chemistry and of official documents that regulate the teaching. In view of this, it is expected that this research may offer reflections on training of future Chemistry teachers, as well as the need for continuing education for teachers already working in education, with emphasis mainly on technologies during Chemistry classes.